2015
DOI: 10.2525/ecb.53.117
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Long-term Exposure to Different O<sub>2</sub> Concentrations on Growth and Phytochemical Content in Red Leaf Lettuce

Abstract: Oxygen gas is one of the environmental factors closely related to photosynthesis and respiration. In this article, we investigated the effects of long-term exposure to different O2 concentrations on growth and phytochemical contents in leaf lettuce. In order for provide exposure to low O2 for longer periods, we developed a new growth chamber combined with N2 gas generator. Plants were hydroponically cultured under 3, 10 or 21% O2. The leaf area of the plants grown at 3% O2 was significantly smaller than that f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
3
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 21 publications
3
3
1
Order By: Relevance
“…Some researchers have reported similar results using leaf lettuce (Iwabuchi et al, 1996;Rajapakse et al, 2009;Kawasaki et al, 2015). In a previous study, we showed that the nitrogen and carbon content was affected by hypoxia treatment, and expected an increase in sucrose content (Kawasaki et al, 2015). In the present study, the decrease of nitrogen and increase of carbon and sucrose content in each leaf under hypoxic conditions was reconfirmed (Table 2).…”
Section: Decrease Of Leaf Areasupporting
confidence: 91%
See 4 more Smart Citations
“…Some researchers have reported similar results using leaf lettuce (Iwabuchi et al, 1996;Rajapakse et al, 2009;Kawasaki et al, 2015). In a previous study, we showed that the nitrogen and carbon content was affected by hypoxia treatment, and expected an increase in sucrose content (Kawasaki et al, 2015). In the present study, the decrease of nitrogen and increase of carbon and sucrose content in each leaf under hypoxic conditions was reconfirmed (Table 2).…”
Section: Decrease Of Leaf Areasupporting
confidence: 91%
“…Moreover, the reduction was induced only during the light period; hence, they speculated that the leaf expansion response was not associated with respiration or photorespiration because C 4 plants concentrate CO 2 in the bundle sheath cells, inhibiting photorespiratory metabolism (Taiz and Zeiger, 2010). We also reported a decrease in leaf area with long-term hypoxia treatment (3% O 2 ) during the light period in red leaf lettuce (Kawasaki et al, 2015). Also, we found a decrease in the specific leaf area of plants grown at 3% O 2 .…”
Section: Introductionsupporting
confidence: 50%
See 3 more Smart Citations